The risk of stroke after bilateral salpingo-oophorectomy at hysterectomy for benign diseases: A nationwide cohort study. (August 2018) - Lai, Jerry Cheng-Yen; Chou, Yiing-Jenq; Huang, Nicole; Chen, Hung-Hui; Wang, Kung-Liahng; Wang, Chien-Wei; Shen, I-Hsuan; Chang, Hung-Chang
Highlights: Oophorectomy at hysterectomy does not increase the incidence of stroke. The administration of estrogen after oophorectomy at hysterectomy reduces the risk of stroke in older women. Young women who do not use estrogen after oophorectomy are not at increased risk of stroke. Abstract: Objective: To assess the risk of stroke (and subtypes of stroke) in women after elective bilateral salpingo-oophorectomy at hysterectomy for benign diseases. Study design: We conducted a nationwide population-based, retrospective cohort study using claims data from Taiwan's National Health Insurance program between 1997 and 2013. Women aged 20 years or more who underwent bilateral salpingo-oophorectomy at hysterectomy for benign diseases (n = 1083) were compared with women who did not undergo bilateral salpingo-oophorectomy at hysterectomy for benign diseases (n = 3903). The follow-up period ranged from 10 to 16 years. Age-adjusted (or unadjusted) and multivariate Cox proportional hazards regression models were used to estimate the risk of stroke between the two groups. Main outcome measures: A diagnosis of stroke (and subtypes of stroke). Results: We did not find a significant association between bilateral salpingo-oophorectomy and the risk of incident stroke (or subtypes of stroke) over an average follow-up of 13 years. Among women aged 50 years or more who used estrogen therapy, the risk of developing stroke was 64% lower in those who had undergone bilateral salpingo-oophorectomy (hazard ratio, 0.36; 95% confidence interval, 0.16–0.79) than in those who had undergone hysterectomy only. Conclusion: This study suggests that the use of estrogen after bilateral salpingo-oophorectomy at hysterectomy for benign diseases reduces the risk of stroke in women aged 50 years or more.